(untitled) (African Journal of Biomedical Research, 2019)
From the chloroform extract of the stem bark of Acacia ataxacantha, a ferrulic acid derivative identified as n-tetradecanyl-3-methoxy-4-hydroxy –trans-cinnamate (tetradecanyl ferulate) compound 2 was isolated for the first time from this plant alongside the triterpene lupenol. The structure of compound 2 was confirmed using NMR and MS and is reported here for the first time. Primary activity of the isolated compound against a panel of disease related protein kinases reveal the compound to be in-active.